2010
DOI: 10.1094/cchem-87-4-0353
|View full text |Cite
|
Sign up to set email alerts
|

REVIEW: Rye Arabinoxylans: Molecular Structure, Physicochemical Properties and Physiological Effects in the Gastrointestinal Tract

Abstract: Cereal Chem. 87(4):353-362Arabinoxylans (AX) are the main dietary fiber (DF) polysaccharides in rye where they represent ≈55% of the total polysaccharides. Rye AX consist of a backbone of (1→4)-β-D-xylopyranosyl residues (X) mainly substituted with α-L-arabinofuranosyl residues (A) to varying degrees at the O-2 position, the O-3 position, or both. The A/X ratio of total AX is 0.49-0.82 and extractable AX ratio is 0.34-0.85 in different studies. AX also contain small amounts of ferulate residues bound to arabin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 75 publications
4
58
0
1
Order By: Relevance
“…For example, the substitution of 50% of refined wheat flour by whole rye flour contributed to an increase in the intakes of total dietary fibre, reaching values of 52% to 56% for men and 79% to 85% for women of AIs. Furthermore, soluble arabinoxylans are the main dietary fibre polysaccharides in rye -around 55% of the total polysaccharides -which could provide a positive influence on the post-prandial glycaemic response (Knudsen & Laerke, 2010). This fact, together with the organic acids derived from the sourdough process could contribute to lowering the glycaemic index in these bread formulations.…”
Section: Effect Of Formulation On Nutritional Value Of Breadmentioning
confidence: 99%
“…For example, the substitution of 50% of refined wheat flour by whole rye flour contributed to an increase in the intakes of total dietary fibre, reaching values of 52% to 56% for men and 79% to 85% for women of AIs. Furthermore, soluble arabinoxylans are the main dietary fibre polysaccharides in rye -around 55% of the total polysaccharides -which could provide a positive influence on the post-prandial glycaemic response (Knudsen & Laerke, 2010). This fact, together with the organic acids derived from the sourdough process could contribute to lowering the glycaemic index in these bread formulations.…”
Section: Effect Of Formulation On Nutritional Value Of Breadmentioning
confidence: 99%
“…Due to the capability of soluble arabinoxylan and β-glucan to increase viscosity, they have physiologically gained a lot of interest as polysaccharides that can attenuate blood glucose and insulin responses and lower blood cholesterol [2,8,9]. Furthermore, the viscosity-elevating properties of arabinoxylan and β-glucan have been shown to slow the rate of gastric emptying and reduce the motility of human small intestine, which may reflect a prolongation of satiety [10].…”
Section: Introductionmentioning
confidence: 99%
“…Botham et al (1998) showed that different glucans yielded different SCFA profi les; fermentation of cellulose produced mainly acetate while pea starch generated less acetate (47%) but more butyrate (36%) and more propionate (15%). Fermentation of arabinoxylan has been associated with a proliferation of the bifi dobacteria, lactobacilli and eubacteria groups and a high proportion of butyric acid in the SCFA produced (Hughes et al 2007, Pastell et al 2009, Knudsen and Laerke 2010.…”
Section: Fermentation Patternsmentioning
confidence: 99%